Pengaruh Pemberian Bantal Penghangat terhadap Tingkat Nyeri Dismenorea pada Remaja Putri - Mila Amaliah; Endiyono Endiyono (Faletehan Health Journal, 2025)
Dysmenorrhea affects daily activities, so it requires treatment to reduce the pain level. One of the treatments that can be done is to use a heating pad. This study aimed to determine the effects of giving heating pads on the dysmenorrhea scale. The study was designed using pre-experiment with pretest-posttest without control approach. A total of 32 respondents were involved in the study, selected by purposive sampling technique. Dysmenorrhea pain was measured using five levels from no pain to severe pain. Data were analyzed using Wilcoxon test. The results showed that before the intervention, the largest percentage of the pain scale was in the severe pain category (46.5%) and after the intervention, the largest percentage of the pain level was in the mild pain category (59.4%). The results of bivariate analysis showed that there was a significant difference (p value = 0.000) between the level of pain before getting a heating pad intervention and after. This showed that heating pads significantly affect the decrease in dysmenorrhea pain level in adolescent girls.